2017
DOI: 10.1007/s00484-017-1424-z
|View full text |Cite
|
Sign up to set email alerts
|

Hair coat characteristics and thermophysiological stress response of Nguni and Boran cows raised under hot environmental conditions

Abstract: Breed, age, coat colour, month and temperature humidity index (THI) influence on body weight (W), body condition score (BCS), thermophysiological variables (rectal temperature (Tr), skin temperature (Tsk)) and hair length was studied in Nguni (n = 19) and Boran (n = 16). As a result of this study, breed influenced W, BCS and Tsk on the neck and belly (P < 0.05). The BCS and W of Nguni cows were higher than the Boran cows. Hair length of both breeds increased from February to August. The THI influenced thermoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Myosin-1a (MYO1A) gene is known as a candidate gene associated with skin pigmentation in cattle [69]. As reported previously, skin pigmentation is highly related to the regulation of body temperature regulation [101,102]. In the enterocyte microvillus, the MYO1A was considered the most abundant actin-based motor protein that interactsinteracting with the apical membrane via a highly basic C-terminal tail domain [103].…”
Section: Myosin-1a (Myo1a)mentioning
confidence: 94%
“…Myosin-1a (MYO1A) gene is known as a candidate gene associated with skin pigmentation in cattle [69]. As reported previously, skin pigmentation is highly related to the regulation of body temperature regulation [101,102]. In the enterocyte microvillus, the MYO1A was considered the most abundant actin-based motor protein that interactsinteracting with the apical membrane via a highly basic C-terminal tail domain [103].…”
Section: Myosin-1a (Myo1a)mentioning
confidence: 94%
“…As an important trait, coat color has a certain selective effect on the production traits of cattle. It has been reported that the weight of cattle with a deep coat color is significantly higher than that of cattle with a light coat color in high-temperature environments [55]. In white pigs, the birth weight of piglets with KIT dominant genotype II was significantly higher than that of piglets with the recessive i allele.…”
Section: Discussionmentioning
confidence: 89%
“…As illustrated in the above applications, the physical and spectral properties of hair and haircoats are inputs to thermodynamic models that predict energy exchange between the animal and the environment [31][32][33][34]. For example, haircoat density acts as a resistance to wind penetration into the haircoat, and thus affects the boundary condition.…”
Section: Habitat Implicatons Of Hair and Haircoat Physical And Spectr...mentioning
confidence: 99%